Recent findings on the impact on Public Health systems of drugs use and abuse (Epidemiology, Biostatistics, and Public Health, 2022)
This special issue of Epidemiology, Biostatistics and Public Health derives from a very strict selection of the more than 100 papers presented at the 8th ISSDP Conference (Rome, CNR, 21-23 May 2014).